Beyond the striae: an atypical case of polymorphic eruption of pregnancy with vasculitic features - Singh, Gautam K.; Baghel, Anshu; Sardesai, Vidyadhar R.; Patki, Anil H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Polymorphic eruption of pregnancy (PEP), also known as pruritic urticarial papules and plaques of pregnancy (PUPPP), is the most common benign dermatosis of pregnancy. We report a case of a 26-year-old primigravida at 32 weeks gestation who developed an extensive pruritic rash initially on the abdomen and later spreading to the extremities, back, flanks, and palms, palpable purpura was observed on the lower extremities, suggesting a vasculitic component. Skin biopsy revealed features of both PEP and leukocytoclastic vasculitis, while direct immunofluorescence for IgA was negative. The patient was managed conservatively with complete recovery. This case highlights a rare presentation of PEP with vasculitic features, necessitating careful evaluation. Further research is needed to explore possible triggers, including immune mechanisms or viral associations, to refine diagnostic criteria and optimize management strategies.